Changes in brain-derived neurotrophic factors in schizophrenic patients with spiritual psychoreligious therapy - Lilin Rosyanti; Indriono Hadi; Akhmad; Teguh Faturrahman; Arip Hidayat (Journal of the Pakistan Medical Association)
Objective: To examine the effect of Spiritual Quranic Emotional Freedom Technique therapy on the level of brain-derived neurotrophic factor in schizophrenic patients.